Ruling Devotion: the hindu temple in the british imperial imagination - Sutton, Deborah (Ranikhet Permanent Black, 2024)
This book is a colonial history of the Hindu temple. Despite the bewildering diversity of places, materials, and structures described by the term (3z(BHindu temple(3y(B, a particular understanding of these edifices emerged during the imperial encounter in India from 1800 onwards. Deborah Sutton presents the defining preoccupations through which colonial understandings of the temple took shape: wealth, sensuality, depravity, and devotion. Her analysis draws on a wide range of literary, visual, and bureaucratic sources to encompass religious, cultural, archaeological, imperial, and art histories.s
Keywords: Archaeology; Art History; Asian Studies